2009
DOI: 10.1086/596738
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection ofPlasmodium falciparumParasites Carrying the Chloroquine-SusceptiblepfcrtK76 Allele after Treatment with Artemether-Lumefantrine in Africa

Abstract: Background Artemether-lumefantrine (AL) is a major and highly effective artemisinin-based combination therapy that is becoming increasingly important as a new first-line therapy against Plasmodium falciparum malaria. However, recrudescences occurring after AL treatment have been reported. Identification of drug-specific parasite determinants that contribute to treatment failures will provide important tools for the detection and surveillance of AL resistance. Method The findings from a 42-day follow-up effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
176
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(216 citation statements)
references
References 41 publications
34
176
5
1
Order By: Relevance
“…29 In our study, the prevalence of wild type Pfmdr-86N genotype was higher than that of Pfcrt-76K following the introduction of ACTs in malaria treatment over a decade ago. This finding is consistent with that of previous studies 30,31 where emergence of wild type 86N genotype preceded that of 76K after implementation of ACT use. Although artemetherlumefantrine is still very effective in malaria treatment in Uganda, 32 analysis of data from different clinical trials showed that high prevalence of wild type Pfmdr-86N parasite genotype is associated with decreased parasite sensitivity to artemisinin-lumefantrine.…”
Section: Discussionsupporting
confidence: 93%
“…29 In our study, the prevalence of wild type Pfmdr-86N genotype was higher than that of Pfcrt-76K following the introduction of ACTs in malaria treatment over a decade ago. This finding is consistent with that of previous studies 30,31 where emergence of wild type 86N genotype preceded that of 76K after implementation of ACT use. Although artemetherlumefantrine is still very effective in malaria treatment in Uganda, 32 analysis of data from different clinical trials showed that high prevalence of wild type Pfmdr-86N parasite genotype is associated with decreased parasite sensitivity to artemisinin-lumefantrine.…”
Section: Discussionsupporting
confidence: 93%
“…Studies in Tanzania have shown that Pfmdr-1 N86 or 184F was selected in reinfections after AL treatment 10 ; furthermore, AL selected Pfcrt K76 and to a lesser extent, the Pfmdr-1 N86 in recurrent infections. 26 In another study performed in Muheza district of Tanzania in 2006, it was reported that 86Y, 184Y, and 1246Y occur more frequently after AQ monotherapy, whereas pre-treatment carriage of N86 or 184F was associated with an increased risk of AL treatment failure. 7 A study from Thailand showed haplotype prevalence of the N86-184F haplotype at 40% in 1988-1993, which increased to 95% in 2003.…”
Section: Discussionmentioning
confidence: 98%
“…This effect of C350R on QN and MQ, however, was not replicated in field isolates, underscoring a complex genetic basis of susceptibility in the field. Another primary determinant of susceptibility to these drugs in P. falciparum is the pfmdr1 gene, which in French Guiana harbors the 86N and 184F residues that are associated with increased LUM susceptibility (31,32). Of note, all isolates remained highly susceptible to LUM, a finding that argues for maintaining the artemether + LUM combination as first-line therapy in the region.…”
Section: Discussionmentioning
confidence: 99%